KAJIAN PENGGUNAAN ASAM PERASETAT UNTUK PEMUTIHAN TERHADAP SIFAT KIMIA PULP BAGASSE HASIL ORGANOSOLV - Sri Hidayati; A Sapta Zuidar (Jurusan Agroekoteknologi Fakultas Pertanian Untirta, 2010)
ABSTRACTBaggase represent waste of lignocellulose yielded by sugar mill after sugar cane taken its. Especial component of bagasse for example fiber about 43-52%, lignine content of 20% and pentosan content of 27%. pulp had been made from bagasse fiber. This research conducted to know the bleaching methode using various concentration peracetic acid viewed from their chemical properties. The bleaching process was carried out using peracetic acid 0, 3, 6, 9, 12 and 15% at 850C for 3 hours. After works, the pulp was washed and dried at room temperature, analyzed for cellulose, hemicellulose and number of kappa. The result showed that higher peracetic acid concentration descreased in cellulose, hemicelluse, lignin, permangant number and kappa number. The best result was obtained at the concentration of 3% with content of cellulose, hemicellulose, and permanganat numer and kappa number of 70,16%, 16,85%, and 30,05 5 respectively.Keywords: bagasse, peracetic acid,cCellulose